Resilience among organ donation coordinators: a Canadian mixed-methods study - Silva, Amina R.; Rochon, Andrea; Hornby, Laura; Lotherington, Ken; James, Lee; Webster, Richard; Sucha, Ewa; Sarti, Aimee; Dhanani, Sonny; Silva e Silva, Vanessa (Frontiers in Public Health, 2024)
Background Organ and Tissue Donation Coordinators (OTDCs) are key to the success of deceased organ donation processes. However, reduced resilience can leave them susceptible to the incidence of work-related issues and decrease the quality of the care provided. Therefore, this study aimed to examine the extent of resilience and influencing aspects among OTDCs in Canada. Methods Mixed-method (QUAN-qual) explanatory sequential design. Quantitative data was collected using an online cross-sectional survey approach with demographic data and the validated scales and analyzed using descriptive and inferential statistics. Qualitative data was collected using a descriptive approach with a semi-structured interview guide and analyzed using content analysis. Results One hundred twenty participants responded to the survey, and 39 participants were interviewed. Most participants from the survey were female (82%), registered nurses (97%) and on average 42 years old. The quantitative data revealed that OTDCs had a high level of perceived compassion satisfaction (ProQOL-CS = 36.3) but a resilience score (CD-RISC = 28.5) lower than other groups of healthcare professionals. OTDCs with over a year of experience in the role were more likely to have higher levels of resilience. The qualitative data identified that participants saw resilience as crucial for their work-related well-being. Although coping strategies were identified as a key factor that enhance resilience, many OTDCs reported difficulty in developing healthy coping strategies, and that the use of unhealthy mechanisms (e.g., alcohol and smoking) can result in negative physical consequences (e.g., weight gain) and reduced resilience levels. Conclusion Participants reported using a series of coping and protective strategies to help build resilience, but also difficulty in developing healthy mechanisms. The lack of healthy coping strategies were seen as contributing to negative work-related issues (e.g., burnout). Our findings are being used to develop tailored interventions to improve resilience and healthy coping strategies among organ donor coordinators in Canada.